Performance of rainfed wheat to nitrogen after early-season soybean in the Alto Paranaiba, region - Silva, Dijalma Barbosa da; Goto, Wilson Shinji (Pesquisa Agropecuaria Brasileira, 1991)
In a field experiment, the performance of rainfed wheat to nitrogen application after early-season soybean was studied in a Dark-Red Oxisoil in the municipality of São Gotardo, Minas Gerais, Brazil. Three cultivars (BR 26 - São Gotardo, MG 1 and BH 1146) were arranged in a split plot scheme in a complete randomized block design with three replications. Sub-pilot treatments were 0 and 40 kg/of N/ha. The cultivar BR 26 not only showed higher grain yield but also its superiority in terms of number of grains/ear and number of spikelets/ear, low plant height and absence of lodging, compared to the other cultivars. Nitrogen application increased grain yield and number of spikelets/ear with a slight increase in lodging.